Leadership in medical emergencies depends on gender and personality - Streiff, Seraina; Tschan, Franziska; Hunziker, Sabina; Buehlmann, Cyrill; Semmer, Norbert K.; Hunziker, Patrick; Marsch, Stephan U (My University, 2011)
NTRODUCTION: Leadership is an important predictor of team performance in medical emergencies. There are no data on why some healthcare workers take the lead in emergencies while others do not. Accordingly, the aim of the study was to determine predictors of leadership in a medical emergency. METHODS: Two hundred thirty-seven medical students in fourth year of medical school participated and filled in a questionnaire assessing knowledge, experience, and personality traits. Students were randomly assigned to 79 groups of three. Each group was confronted with a standardized scenario of a simulated witnessed cardiac arrest. The primary outcome was the predictors of the number of leadership statements during the first 3 minutes of the cardiac arrest. RESULTS: In the first 3 minutes of the cardiac arrest, the participants made a median of five leadership statements (range, 0-22; interquartile range, 2). Thirteen participants (5.5%) made no single leadership statement. Multivariate analysis revealed that male gender (unstandardized coefficient, 1.9; P = 0.01), extraversion (unstandardized coefficient, 0.9; P = 0.02), and agreeableness (unstandardized coefficient, -1.1; P = 0.023) predicted leadership statements. Context knowledge, context experience, and other personality traits had no significant effect on leadership. CONCLUSIONS: During the initial phase of a medical emergency, there is a substantial interindividual variation in the amount of leadership. Leadership behavior as assessed by the number of leadership statements is determined by gender and personality and not by knowledge or experience.